2015
DOI: 10.1371/journal.pone.0122874
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptome Signature of the Receptive Bovine Uterus Determined at Early Gestation

Abstract: Pregnancy success is critical to the profitability of cattle operations. However, the molecular events driving the uterine tissue towards embryo receptivity are poorly understood. This study aimed to characterize the uterine transcriptome profiles of pregnant (P) versus non-pregnant (NP) cows during early pregnancy and attempted to define a potential set of marker genes that can be valuable for predicting pregnancy outcome. Therefore, beef cows were synchronized (n=51) and artificially inseminated (n=36) at de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 46 publications
5
30
1
2
Order By: Relevance
“…The progesterone-induced changes in the endometrial transcriptome seem to be independent of pregnancy status up to the time of conceptus elongation and maternal recognition of pregnancy on day 15 (Forde et al, 2011), but an embryo-dependent programming of endometrial function has recently been demonstrated already from day 7 in the estrous cycle . Also on day 7, Binelli et al (2015) showed endometrial gene expressions in the uterine horn contralateral to an AI that illustrated the readiness and preparedness of the endometrium to receive an incoming embryo. In addition, pretransfer endometrial biopsies from heifers on day 7 of the estrous cycle revealed differences in gene expression according to pregnancy diagnosis in the following cycle after transfer of in vivo derived embryos (Salilew-Wondim et al, 2010) and in vitro produced embryos (Ponsuksili et al, 2012).…”
Section: Preparations In the Embryo Recipientmentioning
confidence: 96%
See 2 more Smart Citations
“…The progesterone-induced changes in the endometrial transcriptome seem to be independent of pregnancy status up to the time of conceptus elongation and maternal recognition of pregnancy on day 15 (Forde et al, 2011), but an embryo-dependent programming of endometrial function has recently been demonstrated already from day 7 in the estrous cycle . Also on day 7, Binelli et al (2015) showed endometrial gene expressions in the uterine horn contralateral to an AI that illustrated the readiness and preparedness of the endometrium to receive an incoming embryo. In addition, pretransfer endometrial biopsies from heifers on day 7 of the estrous cycle revealed differences in gene expression according to pregnancy diagnosis in the following cycle after transfer of in vivo derived embryos (Salilew-Wondim et al, 2010) and in vitro produced embryos (Ponsuksili et al, 2012).…”
Section: Preparations In the Embryo Recipientmentioning
confidence: 96%
“…The hatching is a mutual process, where the embryo is active with collapses and re-expansions, the zona is thinned by secretion of trypsin from the endometrium, and small projections of specialized cellular TE through the zona induce the focal opening(s) through one of which the embryo escapes, aided by TE proteinase secretion (Kirkegaard et al, 2013). In human, an active embryo secretion seems to be essential for establishment of the pregnancy (Brosens et al, 2014).…”
Section: Maternal-embryonic Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In women, endometrial receptivity has been assessed either within a few days prior to the day of ET (Huang et al, 2011) or on the day of ET (Boomsma et al, 2009a). To compare the endometrial transcriptome of cows that would later be determined to be either pregnant or not pregnant, Binelli et al (2015) collected endometrial biopsies on Day 6 after AI from the horn contralateral to the CL.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of these molecules could be used as a prognostic factor to screen and select recipients with endometrial characteristics that favour receptivity. Salilew-Wondim et al (2010) and recently Binelli et al (2015) described the endometrial gene expression around Day 7 post-oestrus in pregnant and non-pregnant cows. Although different methods for sample collection and platform analysis were used in both studies, they concluded that differences in gene expression exist in the number, types of genes and pathways expressed between pregnant cows with receptive endometrium and non-pregnant cows with non-receptive endometrium at Day 7 post-oestrus.…”
Section: Embryo Mortality and Endometrial Receptivitymentioning
confidence: 99%